2018
DOI: 10.1371/journal.pone.0203808
|View full text |Cite
|
Sign up to set email alerts
|

Routine analysis of ascitic fluid for evidence of infection in children with chronic liver disease: Is it mandatory?

Abstract: Ascitic fluid infection is a major cause of morbidity and mortality in cirrhotic patients, requiring early diagnosis and therapy. We aimed to determine predictors of ascitic fluid infection in children with chronic liver disease. The study included 45 children with chronic liver disease and ascites who underwent 66 paracentesis procedures. Full history taking and clinical examination of all patients were obtained including fever, abdominal pain and tenderness and respiratory distress. Investigations included: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Children having ascites are more prone to get ascitic fluid infection therefore special care should be given to children and if there is no signs and symptoms of ascitic fluid infection then ascitic tap should be avoided to prevent development of nosocomial peritonitis. 13,14 Diagnosis of spontaneous bacterial peritonitis is made by culture of ascitic fluid but sometimes culture is negative inspite of ascitic fluid infection and increased neutrophil count in ascitic fluid so culture alone is not sufficient to diagnose SBP hence a study conducted in Egypt studied Amyloid-A in serum and ascitic fluid as a diagnostic marker for SBP. They reported sensitivity and specificity 90% and 60% respectively of ascitic fluid Amyloid-A level for diagnosing SBP.…”
Section: Resultsmentioning
confidence: 99%
“…Children having ascites are more prone to get ascitic fluid infection therefore special care should be given to children and if there is no signs and symptoms of ascitic fluid infection then ascitic tap should be avoided to prevent development of nosocomial peritonitis. 13,14 Diagnosis of spontaneous bacterial peritonitis is made by culture of ascitic fluid but sometimes culture is negative inspite of ascitic fluid infection and increased neutrophil count in ascitic fluid so culture alone is not sufficient to diagnose SBP hence a study conducted in Egypt studied Amyloid-A in serum and ascitic fluid as a diagnostic marker for SBP. They reported sensitivity and specificity 90% and 60% respectively of ascitic fluid Amyloid-A level for diagnosing SBP.…”
Section: Resultsmentioning
confidence: 99%
“…We found that clinical data like maximum liver span, spleen size, fever, and jaundice were important predictors of SBP. For instance, other studies showed that fever was one of the predictors of SBP in children with cirrhosis [ 38 ]. Likewise, laboratory parameters including platelet count, WBC count, and ascitic fluid levels of albumin, were important predictors of SBP in cirrhosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,57 There are limited data on the incidence and characteristics of SBP in children with cirrhosis. The incidence of SBP ranges from 17 to 38% in children with chronic liver disease from single-center experiences, [58][59][60][61][62][63] with only 50% of patients showing symptoms to suggest SBP in one study. 63 In adults, gram-negative organisms such as Escherichia coli and Klebsiella pneumoniae account for up to approximately 60% of positive ascitic fluid cultures; in contrast, grampositive organisms, such as Streptococcus pneumoniae, have been more commonly isolated in children.…”
Section: Diagnosis Of Sbpmentioning
confidence: 99%
“…32 Very few of the published studies in children with infected ascites present data on antimicrobial agents used or antibiotic sensitivity of the bacteria on positive cultures. [58][59][60][61]64,67 Published studies suggest isolated bacteria in ascitic fluid cultures were sensitive to commonly used antibiotics (cefotaxime, ceftriaxone, ciprofloxacin). 65,67 The use of primary or secondary prophylaxis or the use of IV albumin for SBP has not been reported in children.…”
Section: Management Of Sbpmentioning
confidence: 99%